2019
DOI: 10.1073/pnas.1816626116
|View full text |Cite
|
Sign up to set email alerts
|

A cell type-selective apoptosis-inducing small molecule for the treatment of brain cancer

Abstract: Glioblastoma multiforme (GBM; grade IV astrocytoma) is the most prevalent and aggressive form of primary brain cancer. A subpopulation of multipotent cells termed GBM cancer stem cells (CSCs) play a critical role in tumor initiation, tumor maintenance, metastasis, drug resistance, and recurrence following surgery. Here we report the identification of a small molecule, termed RIPGBM, from a cell-based chemical screen that selectively induces apoptosis in multiple primary patient-derived GBM CSC cultures. The ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…Glioma, which is the most prevalent and aggressive primary intracranial tumor, accounts for almost 80% of brain tumors 1,2 . Conventional therapies for glioma include surgical resection, chemotherapy, and radiotherapy 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Glioma, which is the most prevalent and aggressive primary intracranial tumor, accounts for almost 80% of brain tumors 1,2 . Conventional therapies for glioma include surgical resection, chemotherapy, and radiotherapy 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The existence of a stem cell population in glioblastoma is controversially discussed. Although computational work on single cell analytics of clinical specimens suggest that glioblastoma is composed of differentiated cells 2 , recent high profile published work of many others further supported the existence of stem cell-like populations in this disease, being regulated be the microenvironment 48 or specific metabolic 49 , 50 and cell cycle 51 , 52 programs. Inhibiting Notch pathway activity is a powerful strategy to target GSCs 5 , 6 and in experimental studies it has been shown to improve the efficiency of standard of care therapeutic Temozolomide 53 .…”
Section: Discussionmentioning
confidence: 99%
“…High grade gliomas represent a complex and devastating disease and are posing an unmet clinical need. These tumours resist multi-modal therapies and survival times are only 14 months on average (Gregory et al, 2020;Kadiyala et al, 2019;Lucki et al, 2019;Wen and Kesari, 2008). In recent years a lot of focus has been on the complex microenvironment of gliomas.…”
Section: Introductionmentioning
confidence: 99%